Understanding Learning Strategies: A Comparison Between Contextual Learning and Problem-Based Learning - Muhammad Syauqi Jonnata Maftuh; Uthman Shehu Lawal; Moses Ade; Alma Vorfi Lama; Afa Fauzul Adzim (Al-Qalam Institute, 2023)
This study focused on comparing problem-based learning (PBL) and contextual learning (CL) strategies based on findings generated from literature analysis. This study aims to identify essential differences between the two learning approaches and uncover the advantages and limitations of each in an educational context. This research uses a qualitative approach using the library research type—data collection techniques using primary and secondary data sources. The data analysis technique used in this study is descriptive analysis. PBL helps students understand concepts and improve problem-solving and collaboration skills. Meanwhile, contextual learning emphasizes applying knowledge in students' real lives, deepening their understanding. Both of these methods have their advantages. PBL focuses on problem-solving, while Contextual Learning links learning to everyday situations. The best choice depends on the learning context and goals of the student, both of which offer learning experiences relevant to the real world. This research implies the importance of considering and integrating Problem-Based Learning (PBL) and Contextual Learning in student learning experiences.